ADOPTION OF E-WALLET TECHNOLOGY: ANALYZING INNOVATION DIFFUSION FACTORS - Resa Nurlaela Anwar; Cattleya Maharani Kusuma Putri (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Purpose – To analyze the influence of relative advantage, compatibility, complexity, and trialability on the intention to adopt DANA e-wallet. Method – Quantitative approach with multiple linear regression analysis. The purposive sampling technique is used in determining the sample. The data collected through the questionnaire were analyzed and processed using SPSS Version 26. Findings – Simultaneously Diffusion of Innovation has a positive and significant influence on the intention to adopt the DANA e-wallet in East Jakarta. Partially, relative advantage, complexity, and trialability had a positive and significant influence on the intention to adopt DANA e-wallet in East Jakarta, while compatibility had no effect. Originality/Novelty – Combining Diffusion of Innovation (DOI), such as relative advantage, compatibility, complexity, and trialability, with the intention to adopt. Implications – Can provide input for companies in designing more effective marketing strategies according to the market's desires, and can contribute to the design of government policies that support the deployment of inclusive financial technology. In addition, it can assist individuals in making the right decision in adopting e-wallets.